Cancer mortality and morbidity among Lithuanian asbestos-cement producing workers - Smailyte, Giedre; Kurtinaitis, Juozas; Andersen, Aage (Scandinavian Journal of Work, Environment & Health, 2004)
' ' OBJECTIVES ': 'This study investigated the incidence of cancer and cause-specific mortality among workers in the two Lithuanian asbestos-cement factories. ' ' METHODS ': 'The study included 1887 asbestos-cement workers, 1285 men and 602 women, and 37 000 person-years. The two factories were active from 1956 (A) and 1963 (B), and the workers were observed from 1978 to 2000. The analysis was based on a comparison between the observed and expected numbers of cancer and causes of death. The observed numbers of cancer were obtained through linkage with the national cancer registry. The date and causes of death were obtained from two different sources. The expected numbers were calculated on the basis of gender- and age-specific incidence and mortality rates in 5-year periods from the whole country. Standardized incidence ratios (SIR) and standardized mortality ratios (SMR) and 95% confidence intervals (95% CI) were calculated. Duration of employment and time since first exposure were used as indicators of exposure. ' ' RESULTS ': 'During the follow-up, 1978-2000, 473 deaths were observed versus 489 expected. There was no excess risk of deaths from nonmalignant respiratory diseases, except for an elevated risk of mortality in relation to the digestive organs other than cancer, 18 observed versus 12.2 expected (95% CI 0.9-2.3). There was no excess risk for any types of cancer, except for colorectal cancer in men, 17 observed cases (SIR 1.6, 95% CI 1.6-2.6) and one case of mesothelioma in a woman. ' ' CONCLUSIONS ': 'This study on asbestos-exposed workers did not show any excess risk of respiratory cancer or deaths of pneumoconiosis.
Keywords: asbestos; asbestos-cement; asbestos-cement worker; cancer; cancer incidence; chrysotile; Lithuania; morbidity; mortality; worker